Investigation on Coal Slagging Characteristics and Combustion Behaviour in Furnace - Sophia N.J.; Hasini H. (EDP Sciences, 2023)
Coal; Nanotechnology; Assessment tool; Coal characteristics; Combustion behaviours; Historical data; Silica oxide; Slagging characteristics; Softening temperature; Coal combustion